Iridium(iii) complexes as reaction based chemosensors for medical diagnostics. Issue 43 (1st October 2018) - Ma, Dik-Lung; NG, Hing Pan; Wong, Suk-Yu; Vellaisamy, Kasipandi; Wu, Ke-Jia; Leung, Chung-Hang
Abstract : This frontier article introduces recent developments and applications of iridium(iii ) complexes as luminescent probes for ions and biomolecules. Abstract : Transition metal complexes have attracted interest in the fields of cancer therapy, medical and environmental detection, and materials of organic light-emitting diodes (OLED). Recently, iridium(iii ) complexes have been explored in a reaction based way for luminescence monitoring and imaging due to their salient photophysical properties, including large Stokes shifts, long-lived luminescence and high luminescent quantum yields. This frontier article will introduce recent developments and applications of iridium(iii ) complexes as luminescent probes for ions and biomolecules. Our outlook for this class of complexes is also discussed.